Visual Function Score: A New Clinical Tool to Assess Visual Function and Detect Visual Disorders in Children - Sabrina Signorini; Sabrina Signorini; Antonella Luparia; Giulia Cappagli; Eleonora Perotto; Mauro Antonini; Federica Morelli; Federica Morelli; Giorgia Aprile; Elena Ballante; Elena Ballante; Silvia Figini; et al. (Frontiers Media S.A., 2022)
IntroductionA comprehensive assessment of visual functioning at an early age is important not only for identifying and defining visual impairment but also for planning personalized rehabilitation programs based on the visual diagnosis. Since existing tools to evaluate visual functioning present some important limitations (e.g., they are based on qualitative reports, they do not take into account environmental adaptations of visual testing or they have not been formally validated as clinical instruments), the present work has the main aim to propose a new clinical tool (Visual Function Score, VFS) to detect and define visual disorders at an early age.MethodsThe Visual Function Score was administered to one hundred visually impaired children (age range 4 months to 17.75 years old) in the form of a professional-reported protocol for a total of 51 items, each of which is assigned a score from 1 to 9 (or from 0 to 9 in some specific cases). The VFS produces three sub-scores and a global score (from 0 to 100), resulting in a quantitative evaluation of visual functioning.ResultsThe VFS can detect the well-known differences between different types of visual impairment (cerebral, oculomotor, and peripheral or grouped as central and peripheral) and takes into account different environments in the definition of a quantitative score of visual functioning.DiscussionOverall, the use of a quantitative tool to evaluate visual functions and functional vision such as the VFS would be fundamental to monitor the progresses of patients over time in response to rehabilitation interventions.